Experimental study on cold-formed steel shear walls with different corrugated steel sheathings. (December 2022) - Liu, Xiyu; Zhang, Wenying; Yu, Cheng; Li, Yi; Jiang, Ziqin; Yu, Shaole
Abstract: Recent research identified the feasibility of adopting corrugated steel sheets as the sheathing material in the cold-formed steel (CFS) shear wall system. However, different experimental results were reported when using different corrugated cross-sections. To determine the effect of different corrugated steel sheathings on the shear capacities of CFS shear walls, this paper conducted an experimental study on the seismic behavior of corrugated steel sheet sheathed shear walls with different cross-section profiles. The selection of corrugated cross-sectional dimensions was informed by the existing research, including corrugated steel sheets with a rib height of 5 mm, 15 mm, and 38 mm. The experiments involved ten full-scale shear wall specimens evaluated under lateral monotonic loading and cyclic loading. The test results indicate that shear walls with 5 mm-rib-height corrugated steel sheets are most likely to produce shear buckling waves, and therefore have the best ductility and highest utilization of sheathing capacity. Shear walls are more apt to screw connection failure and sheathing local buckling as the rib height increases. There is no obvious difference in the shear capacity between the three types of shear walls due to the premature failure of 15 mm- and 38 mm-rib-height corrugated steel sheets. Sheathing buckling was detected and a substantial increase in the shear capacity was achieved when the reduced screw spacing was adopted in the 15 mm-rib-height corrugated sheet sheathed shear walls. The design of corrugated steel sheet sheathed shear walls needs to consider the influence of both the corrugation and screw arrangement. Highlights: Monotonic and cyclic loading tests on ten full-scale corrugated steel sheets sheathed CFS shear walls were conducted. The influence of different cross-section profiles and screw arrangement were studied. The failure modes, shear capacity, lateral stiffness, ductility, stiffness degradation and energy dissipation capacity of shear walls were analyzed.